Association between lifetime cannabis use and arterial stiffness in a middle-aged general population. Issue 4 (22nd April 2023) - Vallée, Alexandre
Abstract : Background: No studies have investigated the association between arterial stiffness index (ASI) and cannabis use. The purpose of this study is to examine sex-stratified associations of cannabis use and ASI levels in a middle-aged general population. Methods: Cannabis use of 46 219 volunteers of the middle-aged UK Biobank population was assessed by questionnaire and investigates several aspects of cannabis use (lifetime, frequency and current status). Associations between cannabis use and ASI were estimated using sex multiple linear regressions. Covariates were tobacco status, diabetes dyslipidaemia, alcohol status, BMI categories, hypertension, mean blood pressure and heart rate. Results: Men presented higher ASI levels compared with women (respectively, 9.826 vs. 8.578 m/s, P  < 0.001), a higher heavy lifetime cannabis users (4.0 vs. 1.9%, P  < 0.001), higher current cannabis users (3.1 vs. 1.7%, P  < 0.001), higher current smokers (8.4 vs. 5.8%, P  < 0.001) and higher alcohol users (95.6 vs. 93.4%, P  < 0.001). After adjustment for all covariates in sex models, heavy lifetime cannabis users were associated with higher ASI levels in men [b = 0.19, 95% confidence interval (0.02; 0.35)] but not in women [b = –0.02 (–0.23; 0.19)]. Current cannabis users were associated with higher ASI levels in men [b = 0.17 (0.01; 0.32)] but not in women [b = –0.01 (–0.20; 0.18)] and among cannabis users, every day frequency was associated with increased ASI levels in men [b = 0.29 (0.07; 0.51)] but not in women [b = 0.10 (–0.17; 0.37)]. Conclusion: The observed association between cannabis use and ASI could participate in accurate and appropriate cardiovascular risk reduction strategies among cannabis users.